58.6k views
4 votes
Given that f(x) = x sqaured- 13x + 36 and g(x) = x – 9, find (f – g)(x) andexpress the result in standard form.

User Jacquen
by
5.3k points

1 Answer

4 votes

(f-g)(x)=x^2-14x+\text{ 45}

Here, we want to find the result of (f-g)(x)

What we simply want to here is to subtrcat g(x) from f(x)

We proceed as follows;


\begin{gathered} f(x)=x^2-13x\text{ + 36} \\ \\ g(x)\text{ = x - 9} \\ \\ (f-g)(x)\text{ = f(x) - g(x)} \\ \\ (f-g)(x)=x^2-13x\text{ + 36 - (x - 9)} \\ \\ (f-g)(x)=x^2-13x\text{ + 36 - x + 9} \\ \\ (f-g)(x)=x^2-13x-x\text{ + 36 + 9} \\ \\ (f-g)(x)=x^2-14x+\text{ 45} \end{gathered}

User Olivier Samyn
by
5.6k points